IMPROVEMENT OF ANTERIOR CHAMBER STRUCTURE AND CLINICAL OUTCOMES AFTER PHACOEMULSIFICATION IN PATIENTS WITH NARROW-ANGLE GLAUCOMA AND CATARACT (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate improvements in anterior chamber structure and clinical outcomes after phacoemulsification in patients with narrow-angle glaucoma and cataract.Subject and method: This non-controlled, interventional study included 77 patients with narrow-angle glaucoma and coexisting cataract treated at Can Tho Eye and Odonto-Stomatology Hospital during 2024-2026. Parameters assessed before and after surgery included anterior chamber angle width, anterior chamber depth, AOD500, AOD750, TISA500, TISA750, TIA, intraocular pressure, and logMAR visual acuity.Results: Postoperatively, anterior chamber structure improved markedly, with all eyes shifting from angle grades 1-2 to 3-4. Anterior chamber depth increased from 2.45 ± 0.39 mm to 3.57 ± 0.30 mm at 3 months, and AOD500, AOD750, TISA500, TISA750, and TIA all increased significantly. Intraocular pressure decreased from 31.52 ± 9.72 mmHg to 16.61 ± 2.79 mmHg at 1 week and 17.08 ± 2.62 mmHg at 3 months, while visual acuity improved from 1.19 ± 0.81 to 0.32 ± 0.25 logMAR. All changes were statistically significant (p < 0.001).Conclusion: Phacoemulsification in patients with narrow-angle glaucoma and coexisting cataract significantly improved anterior chamber structure, reduced intraocular pressure, and enhanced visual acuity over a 3-month follow-up period.
Keywords: glaucoma, cataract, phacoemulsification, intraocular pressure, anterior chamber structure.